Yoko's show-and-tell - Wells, Rosemary (Disney Hyperion, 2011)
When Yoko's grandparents send her a beautiful antique doll all the way from Japan, Yoko the cat couldn't be happier. She places Miki on a windowsill and brings her candy every day. On Girls' Festival Day, Yoko wants to show Miki to her class and tell them all about the Japanese holiday. In her Big No voice Mama says, "We don't trouble trouble or trouble will trouble us." But Yoko is so excited about Girls' Day that she can't resist taking Miki to school. Mama will never know. What could possibly go wrong?